Lysozyme-Induced Degradation of Chitosan: The Characterisation of Degraded Chitosan Scaffolds - Lončarević Andrea; Ivanković Marica; Rogina Anamarija (Journal of Tissue Repair and Regeneration, 2017)
Up till now, chitosan has confirmed its versatile application in skin, cartilage and bone tissue engineering, as well as in drug delivery applications. This study is focused on enzymatic degradation of porous chitosan structures usually designed for mentioned purposes. In vitro degradation was monitored during four weeks of incubation at physiological temperature and in two different media, phosphate buffer saline solution and water. The scaffolds were characterised before and after enzymatic degradation using scanning electron microscopy and infrared spectroscopy with Fourier transformations (FTIR). According to the gravimetric analysis, higher weight loss of chitosan scaffolds was observed in buffered medium with respect to the water. The results implied that the total weight loss obtained in buffer involves physical dissolution of chitosan and lysozyme cleavage of glycoside bond. Importantly, FTIR identification of chitosan scaffolds after enzymatic degradation indicated the absence of lysozyme activity in water, indicating that weight loss is a result of the chitosan dissolution. This finding greatly impacts design of degradation experiments and characterisation of degradation behaviour of chitosan-based materials utilised as implants or drug delivery systems.
Keywords: chitosan